Theaflavin Ameliorates Cerebral Ischemia-Reperfusion Injury in Rats Through Its Anti-Inflammatory Effect and Modulation of STAT-1 - Fei Cai; Cai-Rong Li; Ji-Liang Wu; Jian-Guo Chen; Chao Liu; Qing Min; Wei Yu; Chang-Han Ouyang; Jin-He Chen (Mediators of Inflammation)
Theaflavin, a major constituent of black tea, possesses biological functions such as the antioxidative, antiviral, and anti-inflammatory ones. The purpose of this study was to verify whether theaflavin reduces focal cerebral ischemia injury in a rat model of middle cerebral artery occlusion (MCAO). Male Sprague-Dawley rats were anesthetized and subjected to 2 hours of MCAO followed 24 hours reperfusion. Theaflavin administration (5, 10, and 20 mg/kg, IV) ameliorated infarct and edema volume. Theaflavin inhibited leukocyte infiltration and expression of ICAM-1, COX-2, and iNOS in injured brain. Phosphorylation of STAT-1, a protein which mediates intracellular signaling to the nucleus, was enhanced 2-fold over that of sham group and was inhibited by theaflavin. Our study demonstrated that theaflavin significantly protected neurons from cerebral ischemia-reperfusion injury by limiting leukocyte infiltration and expression of ICAM-1, and suppressing upregulation of inflammatory-related prooxidative enzymes (iNOS and COX-2) in ischemic brain via, at least in part, reducing the phosphorylation of STAT-1.